P649 Variations in time to clinical presentation for patients with uncomplicated genital gonorrhoea. (14th July 2019) - Ayinde, Oluseyi; Hepburn, Trish; Tan, Wei; Ross, Jonathan
Abstract : Background: Current high rates of gonorrhoea highlight a need for rapid effective treatment. Specifically, reducing the duration between onset of symptoms and presentation for clinical care can prevent the onward transmission of infection and the development of sequelae. We sought to evaluate variation in time to presentation (TTP). Methods: Participants were recruited from 14 clinics across England into the gentamicin for the treatment of gonorrhoea (GToG) trial between October 2014 and November 2016. Demographic, behavioural, and clinical data were analysed from participants presenting with genital discharge and/or dysuria who tested positive for Neisseria gonorrhoeae using a nucleic acid amplification test. Results: 316 participants (269 men) with a median age of 27.6 years (range 16.3–68.4) were included. 194 (61%) were Caucasian, 29 (9%) Black African, 27 (9%) Asian and 66 (21%) of other ethnicities. Median TTP was 4 days (range 1–252) with participants reporting genital discharge (297/316 [94%]), dysuria (251/316 [79%]), genital discharge and dysuria (232/316 [73%]) and 76/316 (24%) additional concurrent symptoms (e.g. rectal bleeding, genital itching). TTP was longer than a week in 24% of participants. Age was inversely correlated with TTP ( rs = −0.276; P = 0.01) and TTP was longer in women compared to men (median 14 vs 3 days; P <0.001), and in those with other symptoms (median 7 vs 3 days; P <0.001). Sexual behaviours comprising same sex partner, higher number of partners, or casual/one-off relationships were associated ( P <0.05) with shorter TTP. TTP was also shorter ( P <0.05) in those with a history of previous gonorrhoea, but not previous chlamydia or history of HIV testing. TTP did not vary ( P ≥0.05) by ethnicity, chlamydia co-infection, amount of discharge, or reported condom use. Conclusion: Specific demographic, behavioural and clinical factors were associated with TTP in individuals with symptomatic gonorrhoea. Detailed knowledge of these factors can be used to prioritise and optimise gonorrhoea management and prevention. Disclosure: No significant relationships.